Analisis Implementasi Program Kelas Ibu Hamil Dengan Inovasi Pemberian Madu Kurma Untuk Penanganan Anemia Di TPMB Veronika Sinaga - Fitriani; Ridni Husnah; Afizah Ratu Amaryllis (Borneo Nursing Journal (BNJ), 2026)
Anemia among pregnant women is a significant global and regional health issue; Batam City has recorded a prevalence of 37%, driven by low adherence to consumption and suboptimal iron absorption from Blood-Supplementing Tablet (TTD) supplementation. This study aimed to analyze the implementation of a "Pregnant Women's Class" program integrated with an innovation involving the administration of date honey to manage anemia among pregnant women at the Veronika Sinaga Independent Midwifery Practice (TPMB) in Batam City. A quasi-experimental design (specifically, a Non-Equivalent Control Group Design) was employed, involving 34 pregnant women in their second and third trimesters with mild to moderate anemia; participants were selected via purposive sampling and proportionally divided into intervention and control groups. Bivariate analysis revealed that the mean hemoglobin (Hb) level rose from 9.42 g/dL pre-intervention to 10.85 g/dL post-intervention, representing a mean difference of 1.43 g/dL. A Paired Sample t-Test yielded a p-value of 0.0001 (p<0.05), demonstrating a clinically significant effect resulting from the integration of this innovation. Biochemical analysis confirms that the combination of iron, B-complex vitamins, and folic acid in dates—synergizing with the high vitamin C and fructose content in honey—acts as a natural enhancer for non-heme iron absorption. This process accelerates erythropoiesis while minimizing gastrointestinal complaints often associated with the side effects of TTDs alone. The study is limited by an evaluation scope focused on a local primary care facility and a monitoring duration of 14 days. It is recommended that practicing midwives adopt the date honey administration innovation within pregnant women's classes as a standard procedure for complementary midwifery care—offering a persuasive, practical, and sustainable approach to alleviating maternal anemia. The study concludes that the implementation of the Pregnant Women's Class, integrated with the innovative administration of date palm honey, is effective and significantly increases hemoglobin levels in pregnant women suffering from anemia at the Veronika Sinaga Independent Midwifery Practice (TPMB) in Batam City.